Organizational Agility according to Strategic Planning Directions A case study in the Ministry of Commerce / General Company for the trade of cars and machinery - علي حسين محـمد حسين; حسين بان عبد الامير (Journal of Economics and Administrative Sciences, 2020)
This research aims at the possibility of rationalizing business organizations according to the strategic planning directions which have been developed to deal with many problems faced by business organizations, including the General Company for Automobile and Machinery Trade which was chosen as a research society, and several research problems were diagnosed, including an increase in the numbers of employees who constitute hidden unemployment, lack of work in the system of job specialization, and the organizational structure which is the non-application of the company to a modern administrative model. The importance of the research is that the company being investigated is a pioneer in its field of work and seeks to achieve customer satisfaction. In order to achieve the objectives of this research, a questionnaire was designed for a deliberate sample of department managers, their assistants, and people’s directors. They numbered (55) individuals, and the five-step scale (Likert) was adopted, and the results were shown based on the SPSS system and the use of statistical tools, mainly the arithmetical mean, the standard deviation, the spearman correlation coefficient, and the results of the research proved the validity of the hypotheses which The theoretical side was based on some studies and research that refer to the concept, objectives and characteristics of strategic planning and organizational agility, as well as personal interviews conducted by the researcher to enhance the research. The statistical tools used have produced a number of conclusions Concerned with the lack of rapid response to environmental changes and selection of cadres of the job in the company randomly is thoughtful and is not suitable for the movement of the environment, as well as identified recommendations, including senior management support on the preparation of studies on competitors and the need to promote their abilities and work according to overall quality management requirements.